Cardiorespiratory Alterations in a Newborn Ovine Model of Systemic Inflammation Induced by Lipopolysaccharide Injection - Nault, Stéphanie; Creuze, Vincent; Al-Omar, Sally; Levasseur, Annabelle; Nadeau, Charlène; Samson, Nathalie; Imane, Roqaya; Tremblay, Sophie; Carrault, Guy; Pladys, Patrick; Praud, Jean-Paul (Frontiers in Physiology, 2020)
Although it is well known that neonatal sepsis can induce important alterations in cardiorespiratory control, their detailed early features and the mechanisms involved remain poorly understood. As a first step in resolving this issue, the main goal of this study was to characterize these alterations more extensively by setting up a full-term newborn lamb model of systemic inflammation using lipopolysaccharide (LPS) injection. Two 6-hour polysomnographic recordings were performed on two consecutive days on eight full-term lambs: the first after an IV saline injection (control condition); the second, after an IV injection of 2.5 μg/kg E. coli LPS 0127:B8 (test condition). Rectal temperature, locomotor activity, state of alertness, arterial blood gases, respiratory frequency and heart rate, mean arterial blood pressure, apneas and cardiac decelerations, and heart-rate and respiratory-rate variability (HRV and RRV) were assessed. LPS injection decreased locomotor activity (p = 0.03) and active wakefulness (p = 0.01) compared to the control condition. In addition, LPS injection led to a biphasic increase in rectal temperature (p = 0.01 at 30 and 180 minutes) and in respiratory frequency and heart rate (p = 0.0005 and 0.005, respectively), and to an increase in cardiac decelerations (p = 0.05). An overall decrease in HRV and RRV was also observed. Interestingly, the novel analysis of the representations of the horizontal and vertical visibility network yielded the most statistically significant alterations in HRV structure, suggesting its potential clinical importance for providing an earlier diagnosis of neonatal bacterial sepsis. A second goal was to assess whether the reflexivity of the autonomic nervous system was altered after LPS injection by studying the cardiorespiratory components of the laryngeal and pulmonary chemoreflexes. No difference was found. Lastly, preliminary results provide proof of principle that brainstem inflammation (increased IL-8 and TNF-α mRNA expression) can be shown 6 hours after LPS injection. In conclusion, this full-term lamb model of systemic inflammation reproduces several important aspects of neonatal bacterial sepsis and paves the way for studies in preterm lambs aiming to assess both the effect of prematurity and the central neural mechanisms of cardiorespiratory control alterations observed during neonatal sepsis.